Rancang Bangun Aplikasi Pembelajaran Surat-Surat Pendek untuk Usia Dini Berbasis Multimedia - Nukholis Abdul Majid; Dewi Tresnawati (Jurnal Algoritma, 2022)
The purpose of this research is to create a desktop-based short letters application. The development of information technology in recent years is very fast. One of the fields that has had a significant impact with this technological development is the field of education, in the process of learning the Koran we are taught to memorize the Koran from these Juz Amma letters. From this problem, the idea emerged to design a short letter learning application for an early age that aims to be a reference in learning and memorizing short letters (Al-Fatihah to Ad-Duha) and learning their meaning using a desktop platform that contains animation. and vocabulary recognition that uses multimedia content, using the Luther-Sutopo version of the Multimedia Development Life Cycle method, the stages used in this research are: Concept, Design, Material Collecting, Assembly and Testing. Data for this research were collected by questionnaire method. Testing of this application consists of Alpha testing, namely testing carried out in the developer environment and beta testing, namely testing by the target user. The results of the test obtained a coefficient value of 84.4 with a very good category. Therefore, this application helps in learning short letters for early childhood accompanied by animation and sound that is in accordance with material that has not been much before, as well as additional vocabulary and tajwid knowledge material by prioritizing visual uniqueness and multimedia features as attractive as possible.